Central neurobiological effects of physical exercise in individuals with chronic musculoskeletal pain: a systematic review. Issue 7 (6th July 2020) - de Zoete, Rutger M J; Chen, Kenneth; Sterling, Michele
Abstract : Objective: Primary objectives: to investigate the central neurobiological effects (using MRI) of physical exercise in individuals with chronic pain. Secondary objectives: (1) to investigate the associations between central changes and clinical outcomes and (2) to investigate whether different types and dosages of physical exercise exert different central changes. Design: Systematic review searching four electronic databases up to September 2018: AMED, CINAHL, Embase and MEDLINE. Two reviewers independently assessed the methodological quality of included studies using the Cochrane Collaboration's Risk of Bias in Non-Randomised Studies-I tool. A standardised extraction table was used for data extraction, which was performed by two reviewers. Interventions: Studies reporting any physical exercise intervention in any chronic musculoskeletal pain condition were included. Eligibility of 4011 records was screened independently by two reviewers, and four studies were included in the review. Primary and secondary outcome measures: Primary outcome: any brain outcome assessed with any MR technique. Secondary outcomes: any self-reported clinical outcomes, and type and dosage of the exercise intervention. Results: All four studies had high risk of bias. There was heterogeneity between the brain areas studied and the types of exercise interventions delivered. All studies reported functional MRI changes in various brain areas following an exercise intervention. Insufficient data were available to conduct a meta-analysis or to answer the secondary aims. Conclusions: Only a limited number of studies were available and all were at high risk of bias. None of the studies was randomised or included blinded assessment. Exercise may exert effects on brain neurobiology in people with chronic pain. Due to the high risk of bias, future studies should use a randomised study design. Investigation of morphological brain changes could be included. PROSPERO registration number: CRD42018108179.